Premier real estate development : does an entrepreneurial orientation for the next generation make this three-family-owned company a good prospect for continuity? - Poza, Ernesto J., 1950- (SAGE business cases., 2023)
Premier Real Estate Development is a family business started by a father and son-in-law in Mexico. Focused now on prime real estate, luxury homes, and premium multifamily buildings, Premier started in 1988 as a small single homebuilder. As it has grown, the business has acquired key nonfamily managers and professionals with core skills, two of whom received significant equity stakes during their tenure and are now managing partners or co-owners. The addition of these two managers makes the company a three-family-owned business. Multiple-partner-families owning a business are common in Latin America, Asia, Europe, and other parts of the world. Premier's three owning family groups are unrelated-even though the founding partners had a relationship by marriage, the elder founder is deceased and his and his son in-law's ownership were consolidated to now represent one family group. The founding vision and the opportunities it generated for all three partners has kept the partnership growing and healthy over time. But as the next generation grows into adulthood, differences in outlook and career objectives among the three families pose a challenge to both continued shareholder loyalty and to a successful succession and continuity of the business under their joint control. Two next-generation members of one partner family want either to work in the business or start their own real estate development enterprise. Next-generation members of the other two families are either uninterested or too young to work or be involved in the company.Students will be asked, much like the partners asked each other, to analyze the benefits and costs of the alternative scenarios and to ultimately choose one to pursue in the interests of the three families involved and the continuity of this valuable and thriving enterprise.